2018
DOI: 10.1186/s12987-018-0106-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the cerebrospinal fluid pressure waveform and craniospinal compliance in idiopathic intracranial hypertension subjects

Abstract: BackgroundIdiopathic intracranial hypertension (IIH) is a condition of abnormally high intracranial pressure with an unknown etiology. The objective of this study is to characterize craniospinal compliance and measure the cerebrospinal fluid (CSF) pressure waveform as CSF is passively drained during a diagnostic and therapeutic lumbar puncture (LP) in IIH.MethodsEighteen subjects who met the Modified Dandy Criteria, including papilledema and visual field loss, received an ultrasound guided LP where CSF pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
1
23
0
1
Order By: Relevance
“…We did not calculate the CSFV–ICP graph and short-term ICC using our method (calculation of ICP and consequently ICC using FSI simulation) because the goal of the present study was to assess ICC in the long term. However, the results of the study by Okon et al in the short term also showed the trend of the CSFV–ICP graph was nonmonotonic ( Okon et al, 2018 ). They used the lumbar puncture to drain CSF, and their measured ICC reached 2.5 ± 1.35 ml/cm H 2 O .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We did not calculate the CSFV–ICP graph and short-term ICC using our method (calculation of ICP and consequently ICC using FSI simulation) because the goal of the present study was to assess ICC in the long term. However, the results of the study by Okon et al in the short term also showed the trend of the CSFV–ICP graph was nonmonotonic ( Okon et al, 2018 ). They used the lumbar puncture to drain CSF, and their measured ICC reached 2.5 ± 1.35 ml/cm H 2 O .…”
Section: Discussionmentioning
confidence: 97%
“…The previous CSFV–ICP graphs were separated into two compensatory reserve zones: the first zone with a lower ICC value and the second zone with a higher ICC value ( Czosnyka et al, 2004 ; Okon et al, 2018 ; Heldt et al, 2019 ). However, compensatory reserve behavior in the corresponding graphs in the present study was variable and not necessarily separated in some ICC zones ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible interpretation of our results is that the venous changes are likely to have had less of an impact due to the changes we see in CSF pulse amplitude. As is well documented within the literature, decreases in CSF pulse amplitude are considered an indicator of increased intracranial compliance [31]. Since increased venous pressure would be expected to increase intracranial pressure, the observed decreases in CSF pulse amplitude and correlated increases in intracranial compliance are not consistent.…”
Section: Discussionmentioning
confidence: 91%
“…The ICP waveform morphology is a significant tool for evaluating intracranial hypertension and compliance [25], [26], [29], [60], [61]. The ICP pulse waveform, thus far studied using the invasive method, can be characterized based on some of the following items [62]- [66] (Figure 3a):…”
Section: B Icp Waveform Parametersmentioning
confidence: 99%